A Case‐Crossover Study of Temperature and Infant Mortality in California. Issue 5 (7th July 2015) - Basu, Rupa; Pearson, Dharshani; Sie, Lillian; Broadwin, Rachel
Abstract Background While most research on temperature and mortality has focused on the elderly, little has concentrated on infants, who may also lack thermoregulatory responses to heat exposure. Methods We examined mean daily apparent temperature, a combination of temperature and humidity, and infant deaths in California during the warm season of May through October 1999 to 2011. Deaths from all causes and specifically from congenital malformations, sudden infant death syndrome, abnormal gestation duration, respiratory causes, and circulatory causes were considered in a time‐stratified case‐crossover analysis of 12 356 infant deaths. Results For all‐cause mortality, excess risk was 4.4% (95% confidence interval −0.3, 9.2) per 5.6°C increase for average of same day and previous 3 days apparent temperature (lag 03). The associations for apparent temperature and both all‐cause mortality and deaths caused by gestation duration were highest for Black infants (13.3%, 95% CI 0.6, 27.6 and 23.7%, 95% CI −3.3, 58.2, respectively), while White infants had elevated risk for deaths from respiratory causes (44.6%; −0.7, 110.5). We further observed differential effects for neonates (infants aged 28 days and under) and post‐neonates (infants above 28 days and under 1 year), and coastal and non‐coastal regions. These associations remained even after considering criteria air pollutants. Conclusions This study suggests that infants are a vulnerable subgroup to heat exposure. Further studies should be conducted with a sufficient number of cases of infant deaths in other locales.